A novel high throughput assay to quantify Epstein-Barr virus neutralizing antibody activity against B-cell and epithelial cell infections for vaccine and therapeutic developments. Issue 26 (9th June 2022) - Li, Fengsheng; Freed, Daniel; Heidecker, Gwendolyn; Galli, Jennifer; Durr, Eberhard; Wang, Dai
Abstract: Epstein-Barr Virus (EBV) is the causative agent of infectious mononucleosis and has been associated with a variety of malignancies. In vivo, EBV infects B cells and epithelial cells. However, the current EBV neutralization assays, especially those against B cell infection, are low throughput, laborious and lack of sensitivity. In this study, we optimized the EBV-GFP based micro-neutralization assay by selecting the most susceptible cell substrates, Akata 4E3 for B cell and HEK293T for epithelial cell. The newly developed procedure is high throughput. The cell type specific neutralization was confirmed using monoclonal antibodies specific to gp350 and gH/gL/gp42. A panel of human sera was also tested. Natural human EBV seropositive sera could neutralize EBV in both B cell and epithelial cell assays efficiently with a majority of human sera generating near 100% EBV neutralization. The EBV neutralizing antibody titers were highly correlated with antibodies specific to gp350, gH, EBV total proteins, and to a less degree with antibodies against gp42. Collectively, we demonstrated this improved neutralization assay is suitable to evaluating the humoral responses elicited by EBV vaccine candidates in preclinical animal models or in large-scale human trials.